The Application of the Pet Protection Law in the Context of Indonesian Law: (A Review of Law No. 18 Of 2009 in Conjunction with Law No. 41 and Criminal Code No. 1 of 2023) - Sukamto Kusnadi; Asmariah Asmariah (PT Publikasiku Academic Solution, 2023)
Animals are living things that can find food and drink by themselves, but if the animal is kept alone or under someone's supervision, then its obligation to provide food and drink and care for it is a form of necessity for people who keep animals. Indonesia is based on law, this is stated in the opening of the 1945 Constitution Article 1 Paragraph 3 states that the State of Indonesia is a country of law. The normative legal research method is used as this research method. By using the legal approach. Secondary sources in research are obtained through books, journals, websites or other related articles. The results of this study are that in the application of the pet protection law, Aris Tangkelabi Pandin was used as a suspect in the case of abuse of a pet belonging to Jally Wenny Mongilala and was sentenced according to the applicable law. In the second case of abuse of dogs, the abuse was committed by Kateni bin Alm Jaimin who lives in Sidomulyo Hamlet, Sidomulyo Village, Selorejo District, Blitar Regency, and was sentenced according to Article 91 b paragraph (1) Jo Article 66 A paragraph (1) Law No. 41 of 2014 concerning Animal Husbandry on Law no. 18 of 2009 concerning Livestock and Health.